Preliminary evidence of age-dependent clinical signs associated with porcine circovirus 2b in experimentally infected CH3/Rockefeller mice - de Castro, Alessandra M.M.G.; Cruz, Taís F. [UNESP]; Yamada, Katarina B.; Gerber, Priscilla F.; Gabardo, Michelle P.; Araújo, João P. [UNESP]; Guedes, Roberto M.C.; Mori, Cinthia K.; Oliveira, Camila P.; Santos, Sueli S.; Richtzenhain, Leonardo J. (Elsevier, 2015)
Mice and rats are susceptible to porcine circovirus 2b (PCV2) infection under field and experimental conditions. However, whether PCV2 induces disease in rodents remains a matter of debate. The objectives of the present study were to determine whether PCV2-induced disease in mice is age-dependent and whether intranasally inoculated animals are able to infect animals they come into contact with. Twenty-five CH3/Rockefeller mice were divided into six groups and intranasally inoculated with 25. μL of either PCV2b or PBS on days 0, 3 and 6. One group remained untreated. Two age groups were tested: 3-week-old mice and 6-week-old mice. The administration of three PCV2 intranasal inoculations at intervals of three days was able to induce infection and support virus transmission in susceptible mice, regardless of the age at inoculation. The clinical signs associated with PCV2 infection were more severe in younger mice, and PCV2-DNA load was higher in their faeces. In conclusion, PCV2 induced disease in mice.
Keywords: PCV2; Rodents; Swine virus; Viral load